Overview of the Factors Affecting the Length of Treatment for Patients with Typhoid Fever in Children at Dr. Tadjuddin Chalid Hospital Makassar in 2018 - Rini Suherti; Andi Sitti Rahma; Trisnawaty (HM Publisher, 2022)
Typhoid fever is one of the endemic diseases in Indonesia caused by Salmonella typhi bacteria. Typhoid fever transmission occurs due to personal hygiene behavior and poor environmental hygiene. Several factors can affect the length of treatment for typhoid fever patients in children. This study was conducted to determine the description of the length of treatment for typhoid fever patients in children at the Dr. Tadjuddin Chalid Hospital Makassar in 2018 based on age, nutritional status, and types of antibiotics. This research is a descriptive study using quantitative methods. The study sample was 75 patients with typhoid fever in children aged 1-18 years. The data was used in the form of secondary data in the form of medical records. The results of the study from 75 patients showed that short length of treatment based on age was found in the 11-14 year age group as many as 22 people (37.3%), the short length of treatment based on nutritional status was mostly found in normal nutritional status as many as 56 people (94.9%), the short length of treatment based on the type of antibiotic was found in the use of the antibiotic ceftriaxone as many as 39 people (66.1%). Most of the length of treatment for typhoid fever patients in children had a short duration of treatment as many as 59 people (78.7%).